2017
DOI: 10.1111/joor.12526
|View full text |Cite
|
Sign up to set email alerts
|

Scalloped tongue is associated with nocturnal intermittent hypoxia among community‐dwelling Japanese: the Toon Health Study

Abstract: Scalloped tongue is considered as a possible clinical finding of obstructive sleep apnoea (OSA). There are few evidence of the association between scalloped tongue and OSA. To examine the association between scalloped tongue and nocturnal intermittent hypoxia (NIH), a surrogate marker of OSA, among a general Japanese population. Study participants were 398 men and 732 women aged 30-79 years who participated in the Toon Health Study from 2011 to 2014. Scalloped tongue was classified into three categories: none,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
1
0
3
Order By: Relevance
“…Tooth marks can be caused by an excessive size of the tongue [27]. Some studies have found that tooth marks are associated with three obesity-related disorders; obstructive sleep apnea [28], nocturnal intermittent hypoxia, and snoring [29], each of which disturb sleep and lead to mental fatigue. In TCM diagnostics, obesity has the symptom of "dampness" (resulting from fat in the body), while a deficiency in qi (vital energy) is marked by fatigue [20].…”
Section: Tooth Marksmentioning
confidence: 99%
“…Tooth marks can be caused by an excessive size of the tongue [27]. Some studies have found that tooth marks are associated with three obesity-related disorders; obstructive sleep apnea [28], nocturnal intermittent hypoxia, and snoring [29], each of which disturb sleep and lead to mental fatigue. In TCM diagnostics, obesity has the symptom of "dampness" (resulting from fat in the body), while a deficiency in qi (vital energy) is marked by fatigue [20].…”
Section: Tooth Marksmentioning
confidence: 99%
“…Język karbowany (łac. lingua crenata) jest terminem opisu jącym charakterystyczną zmianę języka, w której jego brzegi są pofałdowane i z impresjami na jego bocznych powierzch niach [22,23]. Opisane zmiany obserwujemy zarówno obu i jednostronne, w zależności od miejsca przyciskania języka do zębów (ryc.…”
Section: Zmiany Atroficzneunclassified
“…Zmianą współwystępującą jest makroglosja lub obrzęk języka [22]. Nadmierny ucisk tkanek języka w wyniku jego powtarzalnego dociskania do zębów, nadmiernego wypycha nia w przestrzenie międzyzębowe lub ssania języka prowadzi do obecności charakterystycznych impresji na jego bocznych powierzchniach [23].…”
Section: Zmiany Atroficzneunclassified
See 1 more Smart Citation